Nicaea, the nature of God and the construction of knowledge - Venter, Rian (Stellenbosch Theological Journal, 2026)
This article examines operative approaches to knowledge in the 4th century, with a focus on the Council of Nicaea. It explores how such an investigation might be shaped and its implications for defining God amid trinitarian controversies. Informed by the History of Knowledge, Late Antique Studies, Foucault’s insights and contemporary scholarship, the interdisciplinary study addresses a gap in Nicaean scholarship. It briefly engages the “arena of knowledge” – church-state dynamics, Neoplatonic influence, education, and recent research. Four dimensions are analysed: knowledge’s circulation, materiality, form, and character. Aspects such as rhetoric, intellectual agency, friendship, stenography, letters, and anathemas are discussed. Six directions of knowledge in 4th century Christianity are identified, revealing polar tensions that define Nicaea’s distinctive episteme. The article suggests a novel perspective on the study of Nicaea and the doctrine of God while noting the need for further study.